Applied regional growth and innovation models - Nijkamp, Peter; Stimson, Robert; Kourtit, Karima (Advances in Spatial Science, The Regional Science Series, 2014)
Modern spatial-economic systems exhibit a high degree of dynamics as a result of technological progress, demographic evolution or global change. In the past decade, an avalanche of new regional economic growth and innovation models has been put forward. This volume contains a unique collection of operational models of a strong applied nature that may be seen as original landmarks in the rich tradition of spatial-economic growth modelling. The contributors are recognized experts from different parts of the world.